Development of Problem-Based Learning Book for Indonesian Language and Literature Subject at Junior High School - Uun Undarti Septiani; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Universitas Muhammadiyah Ponorogo, 2020)
Problem-based learning connects new problems that exist in daily life. It optimizes the ability to think through the process of group work and experimental activities. The students have difficulties in solving problems. They have little experience and are not highly motivated. It makes them unable to explore what students have. The conventional methods lack of training in critical thinking for students. This causes students to lack confidence to play an active role in the learning process. Based on these problems, the present study therefore developed the Indonesian language learning materials for Grade 7 at the junior high school level using the Problem Based Learning model.